Implementation and Comparison of Elliptic Curve Algorithms in Java - Scholz, Swante

Hegel on the Naturalness of Logic - Ficara, Elena (Argumenta)

PhASAR: An Inter-Procedural Static Analysis Framework for C/C++ - Schubert, Philipp; Hermann, Ben; Bodden, Eric (Proceedings of the 25th International Conference on Tools and Algorithms for the Construction and Analysis of Systems (TACAS 2019), Held as Part of the European Joint Conferences on Theory and Practice of Software (ETAPS 2019))

Revealing the intrinsic geometry of finite dimensional invariant sets of infinite dimensional dynamical systems - Gerlach, Raphael; Koltai, Péter; Dellnitz, Michael (arXiv:1902.08824)
Embedding techniques allow the approximations of finite dimensional attractors and manifolds of infinite dimensional dynamical systems via subdivision and continuation methods. These approximations give a topological one-to-one image of the original set. In order to additionally reveal their geometry we use diffusion mapst o find intrinsic coordinates. We illustrate our results on the unstable manifold of the one-dimensional Kuramoto--Sivashinsky equation, as well as for the attractor of the Mackey-Glass delay differential equation.

Women Philosophers in Early Modern Philosophy - Hagengruber, Ruth Edith (British Journal for the History of Philosophy. Vol. 27)

Kooperation selbst bestimmt? Interdisziplinäre Kooperation und Zielkonflikte in inklusiven Grundschulen und Förderschulen - Neumann, Phillip
Cooperation between teachers and special educators is a central requirement for inclusive schools in which students both with and without special educational needs are taught together. In many studies the autonomy/equity norm is reported as a significant obstacle for cooperation. It implies that teachers strive towards a high amount of autonomy in the sense of ‘privacy in their classroom’ as a reaction to endemic uncertainties of pedagogical work and specific work conditions in schools. Nevertheless, some studies point out that general and special educators strive for and engage in intense forms of cooperation. In this study it is argued from a self-determination theory perspective that cooperation can be accompanied by high values of perceived autonomy if teachers internalized the need for cooperation as part of their professional identity. Furthermore, factors affecting the frequency of cooperation, perception of goal conflict frequency, and stress caused by goal conflicts relating to the endemic uncertainties of pedagogical work are investigated. Analyses were carried out using survey data collected from 222 general and special educators working in either inclusive primary schools, or special schools where pupils had specific special educational needs in the domain of ‘learning’. A key outcome of the study is the absence of the anticipated negative effect of cooperation on the perception of autonomy. This underlines doubts regarding the relevance of the autonomy/equity norm. In addition to that, having special educators with greater levels of experience, as well as the support of the principal through providing fixed time slots for cooperation are identified as central factors supporting cooperation in inclusive schools. Moreover, increased levels of cooperation were found to reduce the perception of goal conflict frequency and stress relating to goal conflicts for general educators. The results of the study are discussed with regard to theoretical implications,the professionalization of general and special educators and opportunities to enhance cooperation and supportive settings in inclusive schools. Die Kooperation von Lehrkräften und Sonderpädagog_innen stellt eine zentrale Bedingung inklusiver Beschulung von Schüler_innen mit und ohne sonderpädagogische Förderbedarfe dar. Als ein maßgebliches Hemmnis der Zusammenarbeit gilt das Autonomie-Paritäts-Muster. Dieses besagt, dass Lehrkräfte aufgrund spezifischer Arbeitsbedingungen und Strukturmerkmale pädagogischer Arbeit in Schule und Unterricht ein hohes Ausmaß an Autonomie i.S.v. ‚Privatheit im Unterricht‘ anstreben. Dennoch weisen Studien darauf hin, dass Lehrkräfte und Sonderpädagog_innen dennoch intensive Kooperationsformen praktizieren und anstreben. In der Arbeit wird mit einem Rückgriff auf die Selbstbestimmungstheorie argumentiert, dass Kooperation auch mit einem hohen Autonomieerleben einhergehen kann, wenn Lehrkräfte und Sonderpädagog_innen Kooperation als Teil ihrer eigenen Professionalität internalisiert haben. Zudem werden Einflussfaktoren auf die Häufigkeit von Kooperation sowie die Wahrnehmung und Belastung von Antinomien und Zielkonflikten als Strukturmerkmale des pädagogischen Handelns untersucht. Grundlage der quantitativ-empirischen Analysen ist eine Stichprobe von insgesamt 222 Lehrkräften und Sonderpädagog_innen in inklusiven Grundschulen und Förderschulen für den Förderschwerpunkt Lernen. Als ein wesentliches Ergebnis der Arbeit zeigt sich, dass negative Effekte der Kooperation auf das Autonomieerleben ausbleiben, sodass die aufgeworfenen Zweifel an der Relevanz des Autonomie-Paritäts-Musters bestärkt werden. Darüber hinaus erweisen sich die Berufserfahrung sowie der Rückhalt der Schulleitung durch geschaffene Zeitfenster im Stundenplan als relevante Einflussfaktoren auf die Häufigkeit der Kooperation von Sonderpädagog_innen in inklusiven Grundschulen. Lehrkräfte in inklusiven Grundschulen nehmen weniger Zielkonflikte und Antinomien wahr und erleben diese weniger belastend, je häufiger sie mit Sonderpädagog_innen kooperieren. Die Ergebnisse werden hinsichtlich theoretischer Implikationen, der Professionalisierung von Lehrkräften und Sonderpädagog_innen sowie Möglichkeiten der Förderung von Kooperation und kooperativer Strukturen diskutiert.
Keywords: Kooperation; Inklusion; Sonderpädagogik; Schulentwicklung; BiLieF

Die sprechende Stadt. Stadtumbau in Paderborn um 1600 und in der Gegenwart - Süßmann, Johannes

Konzeptionelle, strukturelle und inhaltliche Gestaltungsaspekte des Praxissemesters an der Universität Paderborn - Herzig, Bardo; Wiethoff, Christoph (Praxissemester (Religion) in NRW: Bilanz und Perspektiven)

Plunging into a world? A novel approach to undergraduates’ metaphors of reading - Scharlau, Ingrid; Körber, Miriam; Karsten, Andrea (Frontline Learning Research)
Although there is considerable research on and knowledge about students’ conceptual-izations of learning or academic practices and skills, the variability of these conceptu-alizations has been consistently neglected.In the present study, we address this varia-bility in the field of academic readingwith the help of a novel approach. Drawing on qualitative metaphor analysis, we report a detailed system of students’ conceptual met-aphors of reading. Ourspecific methodologicalapproach to identify the structure of these conceptual metaphorsallowsto analyze subjective agency on a lexical as well as grammatical level.The conceptual metaphors we identified by this method are markedly variable, although they create an overall impression of medium to low agency, that is a reader who is only weakly active or potent. Interrater reliability of the coding system was very good. We also report and analyze the frequency of the conceptual metaphors ina sample of 143 texts written by bachelor students.
Keywords: metaphor; conceptual metaphor; metaphor analysis; academic reading; transitivity

Welche Rolle spielen Fachkulturen heute? Bericht von einer Erkundungsstudie. - Scharlau, Ingrid; Huber, Ludwig (die hochschullehre)
With the present exploration, we aimed to answer the question whether distinct disciplinary cultures are present at today’s universities. To this purpose, we conducted 16 interviews with scholars from different disciplines. Qualitative analysis shows that disciplinary cultures in a narrow, epistemological sense (including forms of knowledge and work as well as organisation of teaching and learning) are perceived as distinct aspects of higher education and deemed important. Disciplinary cultures in a broader sense related to lifestyle and habitus, however, were hardly reported and not perceived as characteristic. Questions of social selectivity or inequality within universities were rarely touched in the interviews. Own cultures are typically described as rather heterogeneous, which is not the case for other cultures. Handling of possible cultures as well as differences by the interviewees turned out to be very cautious, at the same time restrained and respectful. Even where differences are observed or different values are revealed, there is little evidence of disputes. Consequences of these findings for research into disciplinary cultures and higher education are discussed.
Keywords: disciplinary culture; habitus; distinctions

A DC bias approach to the characterisation of non-linear material parameters of piezoelectric ceramics - Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd
Keywords: piezoelectric materials; piezoelectric properties; DC bias field; non-linear material parameters

Genericity in Network Dynamics - Schwenker, Sören
This thesis deals with the investigation of dynamical properties – in particular generic synchrony breaking bifurcations – that are inherent to the structure of a semigroup network as well the numerous algebraic structures that are related to these types of networks. Most notably we investigate the interplay between network dynamics and monoid representation theory as induced by the fundamental network construction in terms of hidden symmetry as introduced by RINK and SANDERS. After providing a brief survey of the field of network dynamics in Part I, we thoroughly introduce the formalism of semigroup networks, the customized dynamical systems theory, and the necessary background from monoid representation theory in Chapters 3 and 4. The remainder of Part II investigates generic synchrony breaking bifurcations and contains three major results. The first is Theorem 5.11, which shows that generic symmetry breaking steady state bifurcations in monoid equivariant dynamics occur along absolutely indecomposable subrepresentations – a natural generalization of the corresponding statement for group equivariant dynamics. Then Theorem 7.12 relates the decomposition of a representation given by a network with high-dimensional internal phase spaces to that induced by the same network with one-dimensional internal phase spaces. This result is used to show that there is a smallest dimension of internal dynamics in which all generic l-parameter bifurcations of a fundamental network can be observed (Theorem 7.24). In Part III, we employ the machinery that was summarized and further developed in Part II to feedforward networks. We propose a general definition of this structural feature of a network and show that it can equivalently be characterized in different algebraic notions in Theorem 8.35. These are then exploited to fully classify the corresponding monoid representation for any feedforward network and to classify generic synchrony breaking steady state bifurcations with one- or highdimensional internal dynamics.

Speech Processing for Digital Home Assistance: Combining Signal Processing With Deep-Learning Techniques - Haeb-Umbach, Reinhold; Watanabe, Shinji; Nakatani, Tomohiro; Bacchiani, Michiel; Hoffmeister, Bjoern; Seltzer, Michael L.; Zen, Heiga; Souden, Mehrez (IEEE Signal Processing Magazine)
Once a popular theme of futuristic science fiction or far-fetched technology forecasts, digital home assistants with a spoken language interface have become a ubiquitous commodity today. This success has been made possible by major advancements in signal processing and machine learning for so-called far-field speech recognition, where the commands are spoken at a distance from the sound capturing device. The challenges encountered are quite unique and different from many other use cases of automatic speech recognition. The purpose of this tutorial article is to describe, in a way amenable to the non-specialist, the key speech processing algorithms that enable reliable fully hands-free speech interaction with digital home assistants. These technologies include multi-channel acoustic echo cancellation, microphone array processing and dereverberation techniques for signal enhancement, reliable wake-up word and end-of-interaction detection, high-quality speech synthesis, as well as sophisticated statistical models for speech and language, learned from large amounts of heterogeneous training data. In all these fields, deep learning has occupied a critical role.

PSΦ: Forschungsprogramm zur Studieneingangsphase im Physikstudium - Bauer, Anna; Lahme, Simon; Woitkowski, David; Vogelsang, Christoph; Reinhold, Peter (PhyDid B – Didaktik der Physik – Beiträge zur DPG-Frühjahrstagung)

Updatable Anonymous Credentials and Applications to Incentive Systems - Blömer, Johannes; Bobolz, Jan; Diemert, Denis Pascal; Eidens, Fabian (Proceedings of the 2019 ACM SIGSAC Conference on Computer and Communications Security - CCS '19)
In this paper, we introduce updatable anonymous credential systems (UACS) and use them to construct a new privacy-preserving incentive system. In a UACS, a user holding a credential certifying some attributes can interact with the corresponding issuer to update his attributes. During this, the issuer knows which update function is run, but does not learn the user's previous attributes. Hence the update process preserves anonymity of the user. One example for a class of update functions are additive updates of integer attributes, where the issuer increments an unknown integer attribute value v by some known value k. This kind of update is motivated by an application of UACS to incentive systems. Users in an incentive system can anonymously accumulate points, e.g. in a shop at checkout, and spend them later, e.g. for a discount.

Scaffoldingelemente zur Sprachförderung im Textilunterricht. - Stenzel, Nadja; Drumm, Sandra (ProDaZ)

Lektionen für Alexa & Co?! - Haeb-Umbach, Reinhold (DFG forschung 1/2019)
Wenn akustische Signalverarbeitung mit automatisiertem Lernen verknüpft wird: Nachrichtentechniker arbeiten mit mehreren Mikrofonen und tiefen neuronalen Netzen an besserer Spracherkennung unter widrigsten Bedingungen. Von solchen Sensornetzwerken könnten langfristig auch digitale Sprachassistenten profitieren.

Vorwort: Gender, Technik und Politik 4.0 – Über digitalen Kapitalismus, disruptive Technologien und neue Regime der Unsicherheit - Weber, Jutta (Gender, Technik und Politik 4.0 – Über digitalen Kapitalismus, disruptive Technologien und neue Regime der Unsicherheit, special issue of “Gender“ (Hg.: Jutta Weber/Diana Lengersdorf))

Zur Ehrenpromotion von Maria von Welser an der Fakultät für Kulturwissenschaften der Universität Paderborn - Hagengruber, Ruth (Konsens)
Keywords: Maria von Welser; Women; Media; War; Women in War; Refugees

Tagungsbericht: Musiklandschaften zwischen Pader und Rhein. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Interdisziplinäre Tagung vom 15. bis 17. Juli 2019 in Paderborn - Becker, Rieke; Lauert, Markus; Otto, Arnold